2015
DOI: 10.1007/s10545-015-9811-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in hepatic glycogen storage diseases: pathophysiology, monitoring of dietary management and future directions

Abstract: Hepatic glycogen storage diseases (GSD) underscore the intimate relationship between carbohydrate and lipid metabolism. The hyperlipidemias in hepatic GSD reflect perturbed intracellular metabolism, providing biomarkers in blood to monitor dietary management. In different types of GSD, hyperlipidemias are of a different origin. Hypertriglyceridemia is most prominent in GSD type Ia and associated with long-term outcome morbidity, like pancreatitis and hepatic adenomas. In the ketotic subtypes of GSD, hypertrigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 42 publications
(51 reference statements)
2
43
0
1
Order By: Relevance
“…Hypoketosis has been reported before in GSD III patients (Seigel et al 2008;Clemente Touati et al 2012) et al 2010), in whom exogenous carbohydrate requirements are still relatively high (Derks and Van Rijn 2015). We speculate that, as a consequence of dietary management with frequent high-carbohydrate meals, there may have been a relatively high plasma insulin state together with high intracellular malonyl-CoA levels, physiologically inhibiting long-chain mitochondrial fatty acid oxidation at the level of carnitine palmitoyltransferase type I.…”
Section: Discussionsupporting
confidence: 57%
“…Hypoketosis has been reported before in GSD III patients (Seigel et al 2008;Clemente Touati et al 2012) et al 2010), in whom exogenous carbohydrate requirements are still relatively high (Derks and Van Rijn 2015). We speculate that, as a consequence of dietary management with frequent high-carbohydrate meals, there may have been a relatively high plasma insulin state together with high intracellular malonyl-CoA levels, physiologically inhibiting long-chain mitochondrial fatty acid oxidation at the level of carnitine palmitoyltransferase type I.…”
Section: Discussionsupporting
confidence: 57%
“…This study shows that Pygl ‐deficient mice following a fasting challenge display mild ketotic hypoglycemia along with reduced levels of serum metabolites, including triglyceride, cholesterol, and lactic acid, which can be substrates for GNG. Intriguingly, it has been suggested that elevated ketone bodies in ketotic GSDs reflect increased mitochondria fatty acid oxidation, which is elicited by GNG . Therefore, elevated blood ketone bodies and reduced levels of serum metabolites in fasted Pygl −/− mice raise the possibility that Pygl deficiency may induce GNG instead of defective glycogenolysis to compensate low glucose production in fasted periods, as suggested …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The pathophysiology of these tumors has been related to the underlying metabolic disorder secondary to mutations in the G6PC gene. 3,6 Castleman disease is a rare lymphoproliferative disorder that has never been reported in association with GSD.…”
Section: A Pediatric Patient With Glycogen Storage Disease Type Ia Anmentioning
confidence: 99%
“…Patients with glycogen storage disease type IA (GSD‐IA) have a higher than average risk of developing various abdominal tumors . The pathophysiology of these tumors has been related to the underlying metabolic disorder secondary to mutations in the G6PC gene . Castleman disease is a rare lymphoproliferative disorder that has never been reported in association with GSD.…”
mentioning
confidence: 99%
See 1 more Smart Citation